Graphological Devices and Meaning in Tanure Ojaide’s Poetry - Maledo, Richard Oliseyenum (NIU Journal of Humanities; Vol 4 No 1 (2019): KIU Journal of Humanities, Vol. 4 No. 1, March 2019, 2019)
This study identifies the prominent graphological features in selected poems of Tanure Ojaide. It analyzes and categorizes these prominent graphological features and relates them to the socio-political contexts of the poems. This is with a view to understanding the graphological style of language use in the poems. Our data is drawn from selected poems of Tanure Ojaide and a close analysis of each of the poems is done to elicit graphological features using functional stylistics as our linguistic framework. The result showed that at the level of punctuation, the poet deviates from the usual norm of everyday use as he disregards the use of comma and full stop where convention calls for them. He also avoids the use of capital letters when it is necessary to do so.  He uses these graphological deviations as a means of rejecting and protesting the destruction of his native Niger Delta environment through oil exploration and exploitation; and as a means of expressing his concern for deviant attitude of Nigerian rulers towards the political structure and order. The study concludes that the style which reveals the use of graphological devices projects the inherent messages of the poems. Keywords: graphology, poetry, style, Niger Delta, Tanure Ojaide